1999
DOI: 10.3168/jds.s0022-0302(99)75406-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Accelerated Growth Rates and Estrogen Implants in Prepubertal Holstein Heifers on Estimates of Mammary Development and Subsequent Reproduction and Milk Production

Abstract: The objectives of this study were to determine the effects of accelerating growth rates and of imposing estrogen implants in prepubertal heifers on mammary development and subsequent reproduction and milk production. Sixty-eight Holstein heifers were assigned to 1 of 4 treatment groups by using a randomized complete block design in a 2 x 2 factorial arrangement. The treatments were standard growth rate (700 g/d) or accelerated growth rate (1000 g/d) and estrogen implant or no estrogen implant. The treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
2
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 34 publications
5
57
2
6
Order By: Relevance
“…As reviewed by Velasquez et al (2008), changes in IGF-1 concentrations before puberty are strongly influenced by nutritional regime and are reduced by dietary restrictions, which also delayed puberty. The circulating concentration of IGF-1 is highly correlated to BW and growth rate during the period of pre-pubertal growth (Lammers et al, 1999;Brickell et al, 2009a). In contrast, Garcia et al (2003) found that IGF-1 levels in beef heifers declined in the 10 weeks preceding puberty.…”
Section: Timing Of Pubertymentioning
confidence: 92%
See 1 more Smart Citation
“…As reviewed by Velasquez et al (2008), changes in IGF-1 concentrations before puberty are strongly influenced by nutritional regime and are reduced by dietary restrictions, which also delayed puberty. The circulating concentration of IGF-1 is highly correlated to BW and growth rate during the period of pre-pubertal growth (Lammers et al, 1999;Brickell et al, 2009a). In contrast, Garcia et al (2003) found that IGF-1 levels in beef heifers declined in the 10 weeks preceding puberty.…”
Section: Timing Of Pubertymentioning
confidence: 92%
“…For example, a high energy and protein intake resulted in an increased growth rate and earlier attainment of puberty (Lammers et al, 1999). The review by Gasser (2013) concluded that the growth rate pre-weaning was more important than that post-weaning.…”
Section: Timing Of Pubertymentioning
confidence: 99%
“…Specifically, these problems arise because corn silage is energy dense, and often exceeds the energy requirements for dairy heifers, thereby resulting in excessive weight gains and overconditioning. Previous work has shown that elevated prepubertal ADG has a negative effect on mammary development (Sejrsen et al, 1982), and first-lactation milk yield (Van Amburgh et al, 1998;Lammers et al, 1999;Radcliff et al, 2000). In addition, Hoffman et al (1996) demonstrated that excessive postpubertal growth coupled with early calving also resulted in depressed first-lactation performance.…”
Section: Introductionmentioning
confidence: 91%
“…It also increases fat deposition in the mammary gland in heifers (Capuco et al, 1995;Charles et al, 1999) and in ewes (Johnsson et al, 1986; -E-mail: Lacassep@agr.gc.ca Peclaris et al, 1994Peclaris et al, , 1997Villeneuve et al, 2010). Restricted feeding in the prepubertal period improves milk production in the first lactation in dairy heifers (Foldager and Sejrsen, 1991;Peri et al, 1993;Hohenboken et al, 1995;Van Amburgh et al, 1998;Lammers et al, 1999;Radcliff et al, 2000) and in dairy ewes (Zidi et al, 2005). Umberger et al (1985) and McCann et al (1989) observed that restricted feeding also improved the milk production of meat type breeds (Dorset and Suffolk).…”
Section: Introductionmentioning
confidence: 99%